The effect of interfacial slip on the flexural behavior of steel-bamboo composite beams. (August 2021) - Duan, Yamin; Zhang, Jialiang; Tong, Keting; Wu, Pei; Li, Yushun
Abstract: Steel-bamboo composite I-beams are made of cold-formed thin-walled steel and bamboo-based panels using a structural adhesive. In the structural analysis of these beams, the mechanical properties are considered to be those of integrated beams; however, the effect of slip at the steel-bamboo interface could lead to differences between analytical and experimental results. To investigate flexural behavior, nine steel-bamboo composite I-beams were subjected to monotonic static loadings with two-point symmetric concentrated loads. According to the theory of elementary beam deformation and the differential relationship between interface slip and strain, the equations for calculating the mid-span deflection and flexural capacity of composite beams were established. A comparison between the calculated and experimental results show that steel-bamboo composite I-beams have high bearing capacity and stiffness and the failure modes exhibit ductility, which can be considered in practical engineering applications. Comparing the theoretical results with and without the inclusion of the slip effect, using a transformed section method, it is seen that the mid-span deflection of composite beams with interface slip effect is closer to the real deflection with an increase in accuracy that ranges from 2.64% to 5.95%. The slip effect reduces the stiffness and weakens the flexural capacity of composite beams. The average error between the calculated results with bond-slip and the experimental results is within 10%. Thus, the results of this study serve as a reference for the future design and application of steel-bamboo composite structures.